The Effect of Giving Date Palm Juice (Phoenix Dactykiferal.) and Mung Beans (Vigna Radiata) on The Increasing Hemoglobin of Young Woman in Class XI Students at SMA Negeri 10 Pekanbaru - Yesi Septina Wati; Lira Sismawati Hasibuan (Institute of Computer Science (IOCS), 2021)
Anemia is a condition where the level of hemoglobin (Hb) in the blood is <12 g / dl. Teenagers have a high risk of anemia, especially iron nutritional anemia. Adolescent girls have a higher risk of anemia compared to boys because of some risk factors such as menstruation (too frequent frequency, too much blood coming out, and too long menstruation) etc. One way to overcome it is by food fortification. One of the foods that can prevent iron deficiency is dates and green beans. The purpose of this study was to analyze the effect of administration of dates palm juice and green bean extract on increasing levels of HB adolescent girls. This study uses a pretest and posttest research design with samples 13 respondents of the date palm juice group and 13 respondents of the mung bean juice group, with a sampling technique that is purposive sampling. Analysis of data using t-test dependent test with a degree of confidence <0.05. Statistical results are the influence of giving date palm juice with p value = 0.001 and green bean juice with p value = 0,000. The conclusion is that there is an effect of giving dates palm juice and green bean juice on increasing Hb levels in young women. It is hoped that students will understand correctly about nutritional needs to prevent anemia.